Pengaruh Reputasi Dan Produk Bank Terhadap Keputusan Menabung Pada Bank Mandiri Cabang Sungai Penuh - Pepi Priola; Elvi Nilda; Tiara Tiara (Journal Islamic Economic and Bussines Studies, 2022)
The Bank Mandiri Sungai Penuh pays close attention to the products demanded by its customers. Its outstanding features contribute to its reputation being well-known among the general public. The aim of the research is to determine: 1) the effect of reputation on savings decision at Bank Mandiri Sungai Penuh branch, 2) the effect of the bank's products on savings decision at Bank Mandiri Sungai Penuh branch, and 3) the combined effect of reputation and product on savings decision at Bank Mandiri Sungai Penuh branch. This is a quantitative research. The research variables are Reputation of the Bank (X1), Bank's Products (X2), and Savings Decision (Y). The population is all customers of Bank Mandiri Sungai Penuh branch with a sample of 40 customers. The research instrument is a likert scale questionnaire. Data analysis techniques include Normality Test, Validity Test, Heteroscedasticity Test, Linearity Test, and Multiple Linear Regression Analysis. The results show that reputation (X1) has an impact on savings decision at Bank Mandiri Sungai Penuh branch, as indicated by t-statistic 4.550 < t-table 2.024 and significance level 0.000 > 0.05. Similarly, the bank's product variable (X2) also affects the savings decision variable at Bank Mandiri Sungai Penuh branch, as shown by t-statistic 2.405 > 2.024 and significance level 0.021 < 0.05. The F-test results show that both Reputation and Bank's Products have a combined effect on Savings Decision at Bank Mandiri Sungai Penuh branch, as indicated by F-statistic 317.707 > F-table 3.25 and significance level 0.000 < 0.05.